Impact of co-processing sewage sludge on cement kiln NOx emissions reduction. Issue 4 (August 2021) - Gu, Yunhui; Cao, Haihua; Liu, Wei; Lin, Xiaohu; Zheng, Tao; Cheng, Wei; Huang, Juwen; Xu, Jingcheng
Abstract: Proper management of sewage sludge has become a pressing environmental issue in China in recent years. As an eco-friendly disposal method, co-processing sludge in cement kilns has attracted widespread attention. In this paper, NOx concentration changes in a cement kiln simulation with sewage sludge additions were analyzed experimentally under different temperature and oxygen content levels, and the reaction was studied by FTIR and gas chromatography-mass spectrometry (GC/MS). The most significant reduction of NOx emission was achieved at 900 °C and 3% oxygen content level, with an average reduction of 61.1 mg of NOx per gram of dry sludge and the peak point of NOx emission reduction was at 180 °C, 300 °C, 375 °C and 430 °C. The NOx reduction was mainly attributed to the conversion of NOx to N2 under a certain temperature range by the reducing substances released via the decomposition of free ammonia and protein in sludge. In order to achieve the best conditions for NOx emission reduction, sludge was added to the precalciner in the production test, resulting in an average NOx concentration reduction of 67 mg/m 3 than that without addition of sewage sludge. The study analyzed synergistic treatment sludge reduction effect on NOx emission reduction through multiple experiments. These results provide a guide for the optimal conditions for reducing NOx emissions during the co-processing of sewage sludge in cement kilns. Graphical Abstract: ga1 Highlights: Changes in the NOx emission of cement kiln caused by adding sludge were studied. Maximum reduction of NOx emission was achieved at 900 °C and 3% oxygen content. Reducing substances was produced by free ammonia and protein decomposition in sludge. Sludge was added to the precalciner and NOx concentration reduction was 67 mg/m 3 .